Evaluasi Dan Proyeksi Kebutuhan Pengembangan Terminal Penumpang Bandar Udara Internasional Sultan Mahmud Badaruddin II Kota Palembang, Provinsi Sumatera Selatan Tahun 2022-2037 - Gufron Agung Wijaya; Ari Sandyavitri; Sri Djuniati (Journal of Infrastructure and Civil Engineering, 2022)
Sultan Mahmud badaruddin II International Airport is located in Palembang City, South Sumatra Province. The development of air freight movements at the airport indicates that passenger terminal facilities that have an existing area of 34,000 m2 with a capacity of 3.4 million per year can no longer accommodate the existing passenger volume. This can be seen from the increase in the total number of passengers each year which exceeds capacity to reach 5.1 million passengers in 2018. The study aims to evaluate and analyze projected passenger terminal needs plans for 2022-2037. The development plan is carried out by forming a double linear regression equation between passenger volumes used asdepent variableswhile population numbers (Pdd) and Percapita PDRB on the Basis of Constant Price in 2010 (Pkt) of South Sumatra Province asindependent variables ) with the help of SPSS program version 25.00 and Microsoft Excel. Thus, the number of residents (Pdd) has a greater effect on the growth of domestic passengers. Based on KM Number 10 of 2010 on the Master Plan of Sultan Mahmud Badaruddin II Airport, there needs to be a development of this airport in the future. Based on the results of the development plan of this terminal passenger area in the 2037 plan year of 55. 324m2 with a capacity of 8,871,648 passengers per year and can accommodate 3,177 passengers during peak hours.